A study on awareness on AIDS disease among bachelor degree students of UiTM Sabah / Modh Anizan Jinjah and Mohd Faizal Mohd Nasir - Jinjah, Modh Anizan; Mohd Nasir, Mohd Faizal (2006)
The purpose of this study was to see the level of awareness on AIDS disease among BASc and BBA students at UiTM. 92 respondents participated in the survey. The research objectives are to know the level of awareness on AIDS among bachelor degree students of UiTM, to see the differences on perception, participation, exposure and knowledge on AIDS awareness between male and female bachelor degree students of UiTM and to see the correlation between perception, participation, exposure and knowledge on AIDS among bachelor degree students of UiTM. Respondent's perception, participation level, exposure level and knowledge on AIDS were tested to determine their level of awareness on AIDS disease. This study showed that the knowledge on AIDS disease among the bachelor degree students was not correlated with their perception. However, we found out that the student's knowledge has significant correlation with the student's participation level in AIDS awareness program and Exposure level. We recommended more AIDS awareness activities organized by UiTM to increase their participation and level of awareness on AIDS.